Seasonal response of benthic foraminifera to anthropogenic pressure in two stations of the Gulf of Trieste (northern Adriatic Sea, Italy): the marine protected area of Miramare versus the Servola water sewage outfall - MELIS, ROMANA; CELIO, MASSIMO; BOUCHET, VINCENT M.P.; VARAGONA, GABRIELLA; BAZZARO, MATTEO; CROSERA, MATTEO; PUGLIESE, NEVIO (Mediterranean Marine Science, 2019)
A seasonal survey of living benthic foraminifera was performed in 2013 in the Gulf of Trieste (N Adriatic Sea) to compare two marine coastal sites with different degrees of anthropogenic influence. An assessment of ecological quality statuses showed that the station located near the end of an urban pipeline (Ser station), has worse ecological conditions than the site located in a protected marine area (Res station) all year around. Stressed conditions at Ser station were mainly related to high contents of total organic carbon (TOC) and Zn in the bioavailable fraction, which were a limiting factor for the studied foraminiferal communities. Ammonia tepida, Bolivina spp., and Bulimina spp., which characterised this station, were the most tolerant taxa of the studied assemblage. Conversely, Elphidium spp., H. depressula, N. iridea, Quiqueloculina spp., R. nana and Textularia spp., could be considered less tolerant species as they benefitted from the less stressful conditions recorded at Res station, despite slightly higher concentrations of some potentially toxic elements (PTEs), especially Pb, being recorded in this station in comparison to Ser station. Furthermore, foraminiferal assemblages were found to be quite resilient over an annual cycle, being able to recover from a seasonal unbalanced state to a mature one. The beginning of spring and latest summer would be the best period to assess the ecological quality status to avoid any under- or overestimation of the health of the environment.